已知a+b/a-b=3,则代数式a+b/2(a-b)-3(a-b)/a+b的值为___
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/01 15:44:37
已知a+b/a-b=3,则代数式a+b/2(a-b)-3(a-b)/a+b的值为___已知a+b/a-b=3,则代数式a+b/2(a-b)-3(a-b)/a+b的值为___已知a+b/a-b=3,则代
已知a+b/a-b=3,则代数式a+b/2(a-b)-3(a-b)/a+b的值为___
已知a+b/a-b=3,则代数式a+b/2(a-b)-3(a-b)/a+b的值为___
已知a+b/a-b=3,则代数式a+b/2(a-b)-3(a-b)/a+b的值为___
a+b/2(a-b)-3(a-b)/a+b
=1/2*(a+b/a-b)-3*(a-b)/a+b
=1/2*3-3*1/3
=3/2-1=1/2
已知a-b/a+b=-3,则代数式2(a-b)/a+b-5(a+b)/a-b=?
已知a-b/a+b=-3,则代数式2(a-b)/a+b-5(a+b)/a-b=?
已知代数式a-b=3,则代数式(a-b)^2-5a-5b
已知a+b/a-b=3,则代数式a+b/2(a-b)-3(a-b)/a+b的值为___
已知a-b分之a+b=3,则代数式2(a-b)分之a+b-2(a-b)分之3(a+b)的值为
已知a+b分之a-b=2则代数式3(a+b)分之a-b - a-b分之2(a+b)的值为
已知代数式a+b/a-b=2,那么代数式(3a+3b/5a-5b)-(3a-3b/2a+ab)
已知代数式a+b/a-b=2,那么代数式(3a+3b/5a-5b)-(3a-3b/2a+ab)
已知a-b/a+b=4,求代数式5(a-b)/a+b-a+b/a-b的值
已知9a^-4b^=0,求代数式a/b-b/a-(a^+b^/ab)
已知a-b=1,则代数式2a-2b-3的值是
已知(a*-a)-(a*-b)=2,则代数式2(a-b)+3(a-b)+4(-a+b)+8的值是( )
已知代数式3a+4b=3,求代数式2(2a+b)+5(a+2b)的值
已知a=11,b=11分之一,求代数式a+2a+3a+...+9a+00a+10b+9b+...+3b+2b+b
3、已知(a-b)/(a+b)=2,求代数式2(a+b)/(a-b)-(a-b)/3(a+b)的值
已知(a+b)/(a-b)=2,那么代数式2(a+b)/(a-b)-(a-b)/3(a=b)的值是
已知a*a-ab=3,ab+b*b=-5,求代数式a*a+b*b与a*a-2ab-b*b的值
已知2a-b/a+b=5,求代数式2(2a-b)/a+b + 3(a+b)/2a-b的值是?